2021
DOI: 10.1007/s11547-021-01415-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of CT angiography in detecting acute pulmonary embolism associated with COVID-19 pneumonia

Abstract: Purpose Recently coronavirus disease (COVID-19) caused a global pandemic, characterized by acute respiratory distress syndrome (ARDS). The aim of our study was to detect pulmonary embolism (PE) in patients with severe form of COVID-19 infection using pulmonary CT angiography, and its associations with clinical and laboratory parameters. Methods From March to December 2020, we performed a prospective monocentric study collecting data from 374 consecutive pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Previous reports concluded that PE was more frequent in patients presenting VC [ 34 ]. Nonetheless, our study is the first to look into the detailed configuration of PE regarding AO and VC, providing new insights into possible underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports concluded that PE was more frequent in patients presenting VC [ 34 ]. Nonetheless, our study is the first to look into the detailed configuration of PE regarding AO and VC, providing new insights into possible underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Data from these countries have proven the benefit of a booster dose in reducing symptomatic infection and offering a significant decrease in critical outcomes [ 49 , 50 , 51 , 52 , 53 , 54 ]. Moreover, the protection level offered by previous SARS-CoV-2 infection, both in terms of infection and disease severity and, therefore, of outcome, is still unclear [ 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. In this scenario, the main essential element leading to the evolution of SARS-CoV-2 infection is the interaction with the host’s immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the study by Masselli et al, 26/60 (40%) patients with SARS-CoV-2 were found to be positive for PE at CTPA. In these patients, the probability of being admitted to the intensive care unit was higher than those who did not have PE (19/26 vs. 11/34 patients) and more frequently required mechanical ventilation (15/26 patients vs. 9/34 patients) [45] (Figure 4). and leukocytes, and later thrombin generation and widespread fibrin deposition, are related to the increased risk of thromboembolic events in SARS-CoV2 infection [43,44].…”
Section: Covid-19 Pneumoniamentioning
confidence: 99%